2020
DOI: 10.1021/acsanm.0c02461
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Reinforced Lithium Grease for Antifriction and Antiwear

Abstract: Graphene has attracted tremendous attention as a promising additive in lubricants due to its unique lamellar structure and excellent mechanical strength. Yet, unlike its use in oil and water lubricants, the amount of graphene additive should be considered when it is introduced into the grease which is a two-phase colloid. In this work, graphene was added into the lithium grease in different concentrations, and lubrication behaviors were investigated using a four-ball testing method under various operating cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…In addition, it was shown that solid additives in the grease can enhance the capability of oil retention by interacting with Fig. 10 Results of TG-DTA of the grease thickener [25]. As the grease applied in this study contained the large amount of solid additives, the sealability by this grease could be also enhanced because of the increase in the capability of the base oil retention.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, it was shown that solid additives in the grease can enhance the capability of oil retention by interacting with Fig. 10 Results of TG-DTA of the grease thickener [25]. As the grease applied in this study contained the large amount of solid additives, the sealability by this grease could be also enhanced because of the increase in the capability of the base oil retention.…”
Section: Discussionmentioning
confidence: 78%
“…In summary, the μ value of the lubrication system with G is smaller at higher velocities. This may be due to the high-velocity shearing being more conducive to the spontaneous deposition of G on the friction interface [25]. Hence, a physical transfer film is formed to prevent direct contact between the GCr15 steel block and the ball.…”
Section: Experimental Results Analysismentioning
confidence: 99%
“…In addition, the enhanced wettability of nanofluids contributed to improving tribological properties. Wu et al and Lin et al reported that graphene , and graphene oxide (GO) as nanoadditives contributed toward enhancing friction reduction and wear resistance for Si 3 N 4 /steel sliding pairs. The interfacial tribological properties between SiC and Si 3 N 4 ceramics lubricated by a graphene aqueous solution were investigated by Yuan et al, and it was found that the self-developed graphene exhibited an ultralow FC of 0.009 and an ultralow wear rate of 1.69 × 10 –7 mm 3 /N·m.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the enhanced wettability of nanofluids contributed to improving tribological properties. Wu et al and Lin et al reported that graphene 30,31 and graphene oxide (GO) 32 by Yuan et al, 33 and it was found that the self-developed graphene exhibited an ultralow FC of 0.009 and an ultralow wear rate of 1.69 × 10 −7 mm 3 /N•m. However, the weak dispersity of graphene in an aqueous solution creates a crucial challenge for its further application.…”
Section: Introductionmentioning
confidence: 99%